Analisis Kinerja Keuangan Pemerintah Kabupaten Sleman Pada Tahun 2019-2022 - Najla Aulia Nur Ramadhianti; Cicih Widianingsih; Suci Nasehati Sunaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Based on calculations in financial ratios, this study was conducted to assess the financial performance of the Sleman Regency Government in managing local original revenue in 2019–2022. Secondary data, which includes information from the Cash Flow Statement, Balance Sheet, and Budget Realization Statement, are used. It was taken from https://ppid.slemankab.go.id website. This study used quantitative descriptive data analysis. Referring to the results of data calculations, it shows that cooperation between the Regional Government of Sleman Province and the Central Government in recognizing and solving current problems is less than ideal.